2020
DOI: 10.1049/hve.2019.0388
|View full text |Cite
|
Sign up to set email alerts
|

Multi‐physics analysis and optimisation of high‐speed train pantograph–catenary systems allowing for velocity skin effect

Abstract: A pantograph–catenary system (PCS) – an essential component to supply a high‐speed train (HST) – faces a variety of new challenges due to the continuously increasing train speeds. The HST traction system receives power via an electrical contact between the pantograph strip and the high‐voltage contact wire. This electrical contact is subject to serious mechanical shocks and significant electrochemical corrosion, making the modelling of the dynamic processes complicated, especially under high‐speed and heavy‐lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 37 publications
(33 reference statements)
0
5
0
Order By: Relevance
“…Some scholars also studied the current collection characteristics of carbon strip on the pantograph based on the structure of the pantograph. Liu 20 found when studying the rolling bow head that when the relative movement between the pantograph and the net occurs, the temperature of the carbon strip of the rolling bow head is also weaker than that of the traditional bow head, and when the pantograph and the net system receives the dynamic current, the temperature of the carbon strip of the rolling bow head decreases with the increase of the relative operating speed of the pantograph and the net system, while the temperature of the carbon strip of the traditional bow head increases with the increase of the relative operating speed of the pantograph and the net system; Yao, 21 in order to study the influence of the pantograph slot on the carbon strip, compared the two pantographs with a cavity and the pantographs without a cavity and found that having a closed cavity structure helps to reduce the noise of the pantograph and reduce the wear; Wang 22 explored the length of the train and found that with the increase of vehicles without pantograph, the more serious the complex turbulent zone formed by the carbon strip. From the aspects of air flow and wind direction, Tan, 23 when studying the work of the pantograph, the cylindrical rod perpendicular to the air flow direction has more obvious disturbance effect on the air flow, resulting in a larger range of vortex shedding; Wei 24 studied the arc erosion by studying the lateral wind and found that higher crosswind speed will lead to higher arc voltage, while higher input current corresponds to lower arc voltage, and more accumulated joule heat can significantly reduce the arc resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Some scholars also studied the current collection characteristics of carbon strip on the pantograph based on the structure of the pantograph. Liu 20 found when studying the rolling bow head that when the relative movement between the pantograph and the net occurs, the temperature of the carbon strip of the rolling bow head is also weaker than that of the traditional bow head, and when the pantograph and the net system receives the dynamic current, the temperature of the carbon strip of the rolling bow head decreases with the increase of the relative operating speed of the pantograph and the net system, while the temperature of the carbon strip of the traditional bow head increases with the increase of the relative operating speed of the pantograph and the net system; Yao, 21 in order to study the influence of the pantograph slot on the carbon strip, compared the two pantographs with a cavity and the pantographs without a cavity and found that having a closed cavity structure helps to reduce the noise of the pantograph and reduce the wear; Wang 22 explored the length of the train and found that with the increase of vehicles without pantograph, the more serious the complex turbulent zone formed by the carbon strip. From the aspects of air flow and wind direction, Tan, 23 when studying the work of the pantograph, the cylindrical rod perpendicular to the air flow direction has more obvious disturbance effect on the air flow, resulting in a larger range of vortex shedding; Wei 24 studied the arc erosion by studying the lateral wind and found that higher crosswind speed will lead to higher arc voltage, while higher input current corresponds to lower arc voltage, and more accumulated joule heat can significantly reduce the arc resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Contact pressures that are too large or too small aggravate arc erosion or mechanical wear [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Power transformers are the core equipment in the power transmission systems. During the actual operation of a transformer, its oil-paper insulation system is subjected to electrical, thermal and mechanical stress, and it produces aging characteristics [1][2][3][4]. As a typical aging characteristic, furfural can be used to accurately evaluate the aging degree of the transformer insulation system [5,6].…”
Section: Introductionmentioning
confidence: 99%